Sintesis Mg2+ Doped ZnO dengan Penambahan Albumen Ayam Ras Menggunakan Gabungan Metode Sol-Gel dan Sonokimia - Kasuma Warda Ningsih, Sherly; Kalmar Nizar, Umar; Bahrizal, Bahrizal; Nasra, Edi; Fatimah Mutiara R, Siti (Jurnal Riset Kimia, 2021)
Mg2+ doped ZnO has been successfully synthesized using a combination of sol-gel and sonochemical methods. Zinc acetate dihydrate was used as a precursor, magnesium chloride hexahydrate as a source of Mg dopant, methanol as a solvent, and chicken albumen was used as an additive to replace monoethanolamine. The sol was heated at 110 Â°C for 1 hour. The gel formed was calcined at 600 Â°C for 3 hours. FTIR analysis shows that the absorbance band around 400-450 cm-1 indicates Mg-O stretching, the absorbance band around 500-550 cm-1 indicates Zn-O stretching, the absorbance band around 400-550 cm-1 shows Zn-O-Mg bonds. Mg. Measurements with UV-DRS, obtained the smallest ZnO band gap value doped Mg2+ around 2.7 eV with the addition of 10 mL albumen. The resulting crystal structure was wurtzite with crystal size with the addition of 10, 20, 30, 40 and 50 mL albumen were 25.22-55.91 nm, 32.99-75.87 nm, 45.92-83.91 nm, 45.92-75.89 nm and 46.15-71.47 nm respectively. SEM photo of Mg2+ doped ZnO with the addition of 10 mL of albumen has a hexagonal surface morphology.